2016
DOI: 10.1016/j.expneurol.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Kv1.3 channels to reduce white matter pathology after traumatic brain injury

Abstract: Axonal injury is present in essentially all clinically significant cases of traumatic brain injury (TBI). While no effective treatment has been identified to date, experimental TBI models have shown promising axonal protection using immunosuppressants FK506 and Cyclosporine-A, with treatment benefits attributed to calcineurin inhibition or protection of mitochondrial function. However, growing evidence suggests neuroprotective efficacy of these compounds may also involve direct modulation of ion channels, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 101 publications
4
13
0
Order By: Relevance
“… 56 Demyelination of axons induced by cuprizone or TBI and compression injury also cause increases in refractoriness. 44 , 49 , 57 , 58 …”
Section: Discussionmentioning
confidence: 99%
“… 56 Demyelination of axons induced by cuprizone or TBI and compression injury also cause increases in refractoriness. 44 , 49 , 57 , 58 …”
Section: Discussionmentioning
confidence: 99%
“…Mice were perfused as described for histology and 40 μm coronal brain sections cut by vibratome were processed for IHC [24] using antibodies for IBA1 (Wako, Abcam; 1:300), and GFAP (Dako, Encor Biotechnology; 1:20,000). Images were collected on a Zeiss 700 confocal microscope for qualitative assessment of each protein.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, cumulative studies suggested that Kv1.3 channels took part in the regulation of oligodendrocyte differentiation and maturation . Some Kv1.3 blockers exhibited neuroprotective effects as MBP mRNA decay was completely blocked by the inhibition of Kv1.3 expression . Together, these previous findings indicated that ImK affected the attenuation of oligodendrocyte damage and probably the enhancement of their survival and remyelination.…”
Section: Discussionmentioning
confidence: 86%